Frailty, Mycophenolate Reduction, and Graft Loss in Kidney Transplant Recipients. Issue 4 (April 2015) - McAdams-DeMarco, Mara A.; Law, Andrew; Tan, Jingwen; Delp, Cassandra; King, Elizabeth A.; Orandi, Babak; Salter, Megan; Alachkar, Nada; Desai, Niraj; Grams, Morgan; Walston, Jeremy; Segev, Dorry L.
<x xml:space="preserve">Abstract</x> Background Mycophenolate mofetil (MMF) side effects often prompt dose reduction or discontinuation, and this MMF dose reduction (MDR) can lead to rejection and possibly graft loss. Unfortunately, little is known about what factors might cause or contribute to MDR. Frailty, a measure of physiologic reserve, is emerging as an important, novel domain of risk in kidney transplantation recipients. We hypothesized that frailty, an inflammatory phenotype, might be associated with MDR. Methods We measured frailty (shrinking, weakness, exhaustion, low physical activity, and slowed walking speed), other patient and donor characteristics, longitudinal MMF doses, and graft loss in 525 kidney transplantation recipients. Time-to-MDR was quantified using an adjusted Cox proportional hazards model. Results By 2 years after transplantation, 54% of frail recipients and 45% of nonfrail recipients experienced MDR; by 4 years, incidence was 67% and 51%. Frail recipients were 1.29 times (95% confidence interval [95% CI], 1.01–1.66; P = 0.04) more likely to experience MDR, as were deceased donor recipients (adjusted hazard ratio [aHR], 1.92; 95% CI, 1.44–2.54, P < 0.001) and older adults (age ≥ 65 vs <65; aHR, 1.47; 95% CI, 1.10–1.96, P = 0.01). Mycophenolate mofetil dose reduction was independently associated with a substantially increased risk of death-censored graft loss (aHR, 5.24; 95% CI, 1.97–13.98, P = 0.001). Conclusion A better understanding of risk factors for MMF intolerance might help in planning alternate strategies to maintain adequate immunosuppression and prolong allograft survival.